Assessment of Load Sharing Members in an Anti-Ram Bollard System. Issue 4 (December 2014) - Kinney, Scott; Linzell, Daniel; O'Hare, Edward
Due to the increased frequency, scale, and danger of malicious attacks carried out by Vehicle Borne Improvised Explosive Devices (VBIEDs), anti-ram bollards have become a key element in the protection of critical structures. This study focused on the evaluation of above grade load sharing members in a steel anti-ram bollard system in an attempt to develop efficient load sharing mechanisms that improve the structure's ability to resist vehicle impacts, while concurrently remaining aesthetically pleasing to the general public. A computational assessment was completed using calibrated LS-DYNA finite element models to determine if effective load sharing member configurations and designs could be established so that further optimization of the entire anti-ram system was possible. It was determined that efficient above-grade load sharing could improve the crashworthiness of the anti-ram bollard systems that were studied. Of the configurations that were investigated, the most effective load sharing member design was a single HSS member connecting the vertical bollards near their exposed free ends.